1983
DOI: 10.1021/bi00281a023
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of the cell surface virulent A protein from Aeromonas salmonicida

Abstract: The predominant cell surface protein (A protein) of Aeromonas salmonicida has been purified in high yield from outer membranes by using a combination of detergent and chaotropic extraction methods as well as exclusion and ion-exchange chromatography. The A protein was primarily monomeric, Mr 50 000, but readily formed oligomers at high protein or low salt concentrations. Several isoelectric forms were distinguishable with purified protein as well as in situ on the cell surface. Neither phosphate nor carbohydra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0

Year Published

1985
1985
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 52 publications
3
51
0
Order By: Relevance
“…bacteria, however, the S layer serves as the interface between the parasite and its host, and by virtue of its surface coverage, the S layer is generally the immunodominant protein antigen of the cell (14,33). In the most-studied case, the so-called A layer of the fish pathogen Aeromonas salmonicida, Western blot analysis suggests that the antigenic structure of the S-layer protein is strongly conserved in strains isolated from diverse geographic sources and different fish species and causing different pathogeneses (36). The current study has shown that this is clearly not the situation in C. fetus.…”
Section: Methodsmentioning
confidence: 49%
See 1 more Smart Citation
“…bacteria, however, the S layer serves as the interface between the parasite and its host, and by virtue of its surface coverage, the S layer is generally the immunodominant protein antigen of the cell (14,33). In the most-studied case, the so-called A layer of the fish pathogen Aeromonas salmonicida, Western blot analysis suggests that the antigenic structure of the S-layer protein is strongly conserved in strains isolated from diverse geographic sources and different fish species and causing different pathogeneses (36). The current study has shown that this is clearly not the situation in C. fetus.…”
Section: Methodsmentioning
confidence: 49%
“…Indeed, by using the log-odds score of Dayhoff (11), the two different sequences displayed a mean homology score of 102. Virtually no identity is seen between either of the two C. fetus amino-terminal sequences and the sequences of other S-layer proteins that have been studied, however (16,25,35,36,50), and a search of the National Biomedical Research Foundation protein sequence library (27) failed to reveal any N-terminal sequences with significant homology to those of the C. fetus proteins, suggesting that they are proteins unique to this species.…”
Section: Methodsmentioning
confidence: 97%
“…Figure 7 shows that when the S-layer proteins were incubated with endoproteinase Glu-C, a series of peptides in the approximate Mr range of 5,000 to 48,000 were detectable by SDS-PAGE. The electrophoretic profiles of the various S-layer proteins displayed pronounced differences in their electrophoretic banding profiles in terms of (33).…”
Section: Resultsmentioning
confidence: 99%
“…Amino acid composition of the antigen showed characteristic features usually found in RA proteins of various bacteria (13,19,22,29) : the predominance of acidic amino acids, the low contents of methionine and histidine, and the lack of cysteine. These remarkable features were also found in the composition of antigen S of C. botulinum type A 190L (31).…”
Section: Discussionmentioning
confidence: 97%